POTENSI PEMANFAATAN DAUN PEGAGAN DAN PATI JAGUNG MENJADI BEDAK DINGIN - Nuryati Nuryati; Ema Lestari; Naca Susana Ludiah (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
Pegagan plant (Centella asiatica (L) Urban) is one of the medicinal plant that has many benefits, so it attracts the attention of experts to research and develop it in the context of exploring new drugs that come from nature. The porpose of researc was to formulate between pegagan leaves and corn patch in the manufacture of cold flour and characterize pegagan leaves and corn patch. The research of method was carried out, making corn starch, making cold powder, and the tests carried out were hedonic tests, irritation tests and adhesion tes,. The results obtained from the Hedonic power test from the best treatment are the colors for F1 treatment which is 3.87, F1 texture which is 4.20 and aroma at F3 which is 5. Adhesion test results obtained are 182.49 seconds of F1 action, and irritation test in F1 treatment, it was found to be negative (-) or no irritation.